Sentiment Analysis System Of Bali Tourism Using Naive Bayes Algorithm And Web Framework - Utami, Nengah Widya; Purnama, I Nyoman; Prayoga, I Made Ari (SEAN Institute, 2024)
To obtain trends and impacts that may occur in the Bali tourism industry after the pandemic requires tourism actors to maintain the existence of the tourist beauty and culture they have. This research aims to develop a sentiment analysis system in the Bali tourism sector using the Naive Bayes algorithm and the Web Framework. This research stages carried out include Data Collection (Scraping), Data Cleaning, Feature Extraction, Modeling, and Web Platform Development. The data used was 2779 review data. The results show that most of the visitor reviews are in the